PENGARUH PROMOSI, PENILAIAN PRODUK DAN LAYANAN COD TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Konsumen E-Commerce Shopee Di Cikarang Barat) - Husein Tuasikal; Eko Sugiyanto; Irwan Faedy (JURNAL LENTERA BISNIS, 2024)
This study aims to determine the effect of promotion, product assessment, and COD services individually (partially) and simultaneously on purchasing decisions for e- commerce Shopee consumers in Danau Indah Village, West Cikarang sub-district. The sample in this research is 110 respondents. The technique used is purposive sampling, non-probability sampling. The data collection technique uses a questionnaire that has been tested for validation and reliability. The analysis technique used is multiple linear regression analysis. The results of this study indicate that: (1) Promotion has a positive and significant effect on purchasing decisions for e- commerce Shopee consumers in Danau Indah Village, West Cikarang District, as evidenced by the Promotion variable (X1) having a coefficient (β1) = 0.254 > 0 t count 2.636 > t table 1982 and significant (0.010) < 0.05. (2) Product assessment has a positive and significant effect on purchasing decisions for Shopee e-commerce consumers in Danau Indah Village, West Cikarang District, as evidenced by the product evaluation variable (X2) having a coefficient (β2) = 0.783 > 0 t count 9.224 > t table 1.982 and significant (0.000) < 0.05. (3) COD services have a positive and significant effect on purchasing decisions for Shopee e-commerce consumers in Danau Indah Village, West Cikarang District, as evidenced by the COD service variable (X3) having a coefficient (β3) = 0.250 > 0 t count 2.157 > t table 1.982 and significant (0.033) < 0.05. (4) Promotion, Product Assessment, and COD services have a positive and significant effect on purchasing decisions for e-commerce Shopee consumers in Danau Indah Village, West Cikarang District, as evidenced by the variable F count value 63.560 > F table 2.69 and the significance is 0.000